O canto da igreja “em saída” : uma releitura da Evangelii Gaudium à luz do magnificat - Paiva, Vinícius da Silva (2023)
This master’s thesis The Church’s Song “which goes forth” performs a re-reading of the Apostolic Exhortation Evangelii Gaudium in the light of the Magnificat (Lk 1,46-55) in an ecclesiological perspective. In the first part, a hermeneutic study is presented on the biblical figure of Mary of Nazareth, on the narrative of the visitation (Lk 1,39-45) and the song of the Magnificat itself. In the second part, the genesis and theological roots of Pope Francis’ thought are investigated. It is an ecclesiology that values the mystery of the Incarnation, the inculturated faith, the maternal vocation of the Church and popular piety. The four principles presented by Francisco in the EG are deepened: time is superior to space; unity prevailed over conflict; reality is more important than an idea; and the whole is greater than the part. Francisco’s dialectic is presented in the research as a “polyhedral view of reality”, through which it becomes possible to overcome polarization, respecting differences. In the third part, the decisive role that the Holy Spirit plays in Francis’ ecclesiology is highlighted, whether in popular mysticism or in the synodal path of the Church. In the light of the Magnificat, we seek to indicate applications of EG in pastoral, social and planetary dimensions; and demonstrate that there is no break between joy and prophecy, between praise and social commitment. Concrete pastoral issues are addressed and ecological conversion and inclusive evangelization are proposed as pastoral paths for the Church “which goes forth” of the 21st century. At the end, based on the research carried out on the EG and the Magnificat, some contributions are briefly offered regarding the missionary ecclesial communities.